2020
DOI: 10.1007/s12028-020-01103-1
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width is Associated with 30-day Mortality in Patients with Spontaneous Intracerebral Hemorrhage

Abstract: Background Red cell distribution width (RDW) has been associated with mortality and outcome in a wide variety of non-neurological and neurological diseases, namely in myocardial infarction and acute ischemic stroke, and the reason for this is not completely understood. We aimed to investigate RDW as a potential prognostic marker in patients with intracerebral hemorrhage (ICH). Methods This is a retrospective study of consecutive patients with acute non-traumatic ICH admitted to a single center during a 4-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…In patients undergoing ischemic stroke, RDW predicts worse neurological improvement and mortality (37,38). RDW also shows predictive performance in hemorrhagic cerebrovascular diseases like spontaneous intracerebral hemorrhage (39) and aSAH (7)(8)(9), the latter of which our study focused on.…”
Section: Discussionmentioning
confidence: 73%
“…In patients undergoing ischemic stroke, RDW predicts worse neurological improvement and mortality (37,38). RDW also shows predictive performance in hemorrhagic cerebrovascular diseases like spontaneous intracerebral hemorrhage (39) and aSAH (7)(8)(9), the latter of which our study focused on.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, RDW is closely related to the outcome of carotid atherosclerosis and ischemic stroke (Chugh et al, 2015;Li et al, 2017;Turcato et al, 2017). It is also reported that RDW is an independent predictor of 30-day mortality in ICH patients (Pinho et al, 2021). Altintas et al (2017) showed elevated RDW levels to be significantly positively correlated with hematoma growth in a retrospective study based on 60 patients with cerebral parenchymal hemorrhage.…”
Section: Discussionmentioning
confidence: 92%
“…A routine complete blood count is the most commonly measured laboratory test in hospital, for the advantage of being widely available, non-invasive, easy, economical, and rapid to perform ( Gilev et al, 2017 ). Several studies have shown the significance of red blood cell (RBC) indices in predicting mortality, clinical outcomes, and functional rehabilitation after stroke ( Roh et al, 2019 ; Pinho et al, 2021 ). In addition, increasing evidence suggests that RBC indices may also be indicative of cognitive impairment ( Dlugaj et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] An RDW study of the short-term prognosis after stroke showed that higher RDW was associated with poor function at discharge or 3 months later and that RDW had a dose-dependent relationship with 3-month mortality. [15][16][17][18] There have also been studies on the relationship between RDW and the prognosis of patients with large artery cerebral infarction. These found that RDW is associated with 1-month mortality in patients with malignant middle cerebral artery infarction 19 and that high RDW is a poor prognostic factor.…”
Section: Introductionmentioning
confidence: 99%